PENGARUH LATIHAN BRIDGING DAN TIGHTROPE WALKER TERHADAP KESEIMBANGAN DINAMIS PADA ANAK USIA PRASEKOLAH (3-6 TAHUN) - Siregar, Wilda Wahyuni; Rahmawati, Siti; Octavariny, Raisha; Hayati, Kardina; Ginting, Luci Riani; Aritonang, Juneris (Jurnal Reproductive Health, 2022)
The results of the Basic Health Research (Riskesdas) in 2013 showed that the percentage of children with gross motor development disorders in Indonesia was 12.4%. The child's ability to move (motor) is closely related to one aspect of motion, namely dynamic balance. Dynamic balance is the ability to maintain balance when the body is moving. Any disturbance in balance will affect the child's ability to carry out activities. Balance is the integration of the visual, somatosensory and musculoskeletal systems that will adapt to the environment. This system develops during childhood. Until 10 years, control of dynamic balance in children is not as excellent as in adults. This study was to determine the effect of giving bridging and tightrope walker exercises for dynamic balance in preschoolers. This study is a quasi-experimental with a pre-test & post-test one group design. The sample in this study was 11 children of preschool age at Posyandu Regensi Pratama Depok. The treatments were bridging and tightrope walker exercises. The bridging exercise should be done with holding for 5 seconds, gradually increasing to 10 seconds for 3 sets of 10 repetitions with a rest time between sets of 10 seconds. Meanwhile the tightrope walker exercise is done for 10 repetitions. Training sessions were conducted 2 times a week for 6 weeks. The measuring instrument used is PBS (Pediatric Balance Scale). The research data obtained p value = 0.003 which means that bridging and tightrope walker exercises can increase the level of dynamic balance in preschooler children (p <0.05). The results of this study can be used as a reference to make exercise programs for dynamic balance in preschooler children.